Handbook of Nonsexist Writing for Writers, Editors and Speakers; Marketing to Women ; Microcomputer Primer (First Edition): A Layman's Guide for Selection and Use of Microcomputers in Developing Countries - Dennis Hinkamp; Joe Courson; Jim King (Journal of Applied Communications, 1985)
Reviews of "The Handbook of Nonsexist Writing for Writers, Editors and Speakers by Casey Miller and Kate Swift; "Marketing to Women," by Cecelia Reed, Mark Sullivan and Neal Hirschfeld; and "Microcomputer Primer (First Edition): A Layman's Guide for Selection and Use of Microcomputers in Developing Countries," by John L. Woods.